Shade Selection of Indigofera zollingeriana Miq Putative Mutant: Evaluation of Plant Growth, Biomass Production, Nutrient Contents, and In Vitro Digestibility - Royani, J. I.; Abdullah, L.; Sudarsono; Aisyah, S. I.; Hardianto, D.; Negoro, P. S.; Purba, R. D.; Azahra, B. S. (Tropical Animal Science Journal, 2025)
The use of gamma rays to improve Indigofera zollingeriana is beneficial for developing new superior varieties with genetic characteristics inheritable by other generations. During the development, selecting genotypes from I. zollingeriana putative mutant under shaded conditions can create stable shade-tolerant varieties, with the potential to be developed into new cultivars. Therefore, this study aimed to explore the selection of I. zollingeriana putative mutant in the M2 generation for assessing and evaluating plant growth performance, biomass production, as well as nutrient content and digestibility under shading. Seedlings of 10 I. zollingeriana putative mutants along with 2 control plants, were subjected to 5 levels of shade, namely 0%, 55%, 65%, 75%, and 85%, to identify genotypes with shade tolerance. The results showed that shading significantly (p<0.05) increased plant height, chlorophyll content, leaf length, and leaf width, but decreased the number of leaves, nodes, stem diameter, and branches, also leading to decreased biomass production, high nutritional content, and improved digestibility values. Genotypes R4.10 and R5.10 showed enhanced plant growth, stable biomass production, and increased nutritional content, with low digestible neutral detergent fiber (dNDF), and higher in vitro true digestibility (IVTD) values compared to control under shaded and unshaded conditions. The identified superior genotypes are promising for breeding programs and practical application in agroforestry or silvopasture systems.